Cytotoxicity Evaluations on Vitex negundo Anti-inflammatory Extracts - N.M, Yunos; Ali R, Mat; O.B, Kean,; R, Abas (Malaysian Journal of Science, 2005)
Vitex negundo that is locally known as legundi has been used traditionally as tonic, febrifuge and anti-inflammatory medicaments. FRIM already made an attempt to proof its anti-inflammatory activities. V. negundo dichloromethane and ethanolic extracts were scientifically proven for its anti-inflammatory activities through TPA-induced mouse ear oedema assay with percentage of inhibition 72.2% and 54.1 % respectively. Cytotoxicity effects on these anti-inflammatory extracts were evaluated using sulphorhadamine B (SRB) assay on mammary (MCF-7 cell line) and genito-urinary (VERO cell line) systems. Based on WHO 1972, extracts with IC₅₀ values less and equal to 20 µg/ml can be preliminary considered as cytotoxic. The IC₅₀ values of the extracts on both cell lines were more than 50 µg/mI. Hence, these anti-inflammatory extracts were not cytotoxic on both mammary and genito-urinary systems teste.